Socialising of Harmonising Tax Regulation for Micro, Small and Medium Enterprises (MSMEs) in the Village of Kerinjing - Fuadah, Dr. Luk Luk; Kalsum, Umi; Safitri, Rika Henda; Wahyudi, Tertiarto; Mukhtarudin (Faculty of Economics, Universitas Sriwijaya, 2024)
The aim of this community service is to give a better understanding of harmonizing tax regulations on micro, small and medium enterprises (MSMEs) in the village of Kerinjing. Tax assistance related to the Socialisation of Harmonisation of Tax Regulations for MSMEs in Kerinjing Village, Tanjung Raja Sub-district, Ogan Ilir Regency that will be carried out aims to provide information and for MSMEs based on applicable provisions both those regulated in Law N0. 7 of 2021 concerning Harmonisation of Tax Regulations. The implementation team made three visits for location surveys, implementation and evaluation of community service activities. Implementation of this community service is on 26 October 2022. The number of participants was 30 people. Implementation methods are lectures, tutorials and discussions. During the implementation, questions and answers and discussions were held to see the understanding of the activity participants. From the results of the service activities, it is clear that there are still many MSME actors who do not yet have an understanding of the harmonization of tax rules. Micro, Small and Medium Enterprises (MSMEs) are expected to report their business tax results as well as possible and to refer to the current tax laws and regulations. The socialisation of harmonisation of tax regulations for MSMEs in Kerinjing Village provided participants with an understanding of the definition of tax, the subject and object of income tax and also provided participants with an understanding of tax obligations related to income tax and value added tax.